THE POSITION OF SONS IN THE MANDAILING FAMILY IN RANTAUPRAPAT - Yana Restika Siregar; Yummy Jumiati Marsa; Syarbaini Saleh (UNIVERSITAS PAKUAN, 2022)
This study aims to describe the position of sons in the Mandailing family in overseas areas. This research is located in Bangun Sari Hamlet, Labuhanbatu Regency, Rantauprapat. This study uses an ethnographic approach using descriptive qualitative methods. The subjects in this study were married couples (families) who are of the Mandailing ethnicity. The number of respondents in this study were 5 people. Data collection was carried out by observing, interviewing, and studying written documents. The data obtained was then analyzed using qualitative data analysis, namely data collection, data reduction, and data presentation. Research results obtained by children in a family are the most beautiful gifts from God. In a family in the Mandailing community, sons are very important because sons carry a surname and are successors of the genealogy and are a complement to the philosophy of Dalihan Na Tolu. The Mandailing ethnic community in Bangun Sari Hamlet has an understanding that the position of sons in the Mandailing family is high because they are the successors of the clan. However, along with the times and the occurrence of assimilation in customs and culture with the Javanese, the people view boys and girls as the same. There is no difference in what happens to girls even though sons are the successors of the clan. In the past, boys were number one in education and wealth, but now they are all equal